Multiplex PCR for simultaneous genotyping of kdr mutations V410L, V1016I and F1534C in Aedes aegypti (L.) - Villanueva Segura, Karina; Ponce García, Gustavo; López Monroy, Beatriz; Mora Jasso, Esteban de Jesús; Perales, Lucia; González Santillán, Francisco Javier; Ontiveros Zapata, Kevin Aarón; Dávila Barboza, Jesús Antonio; Flores, Adriana E. (BioMed Central, 2020)
Abstract Background Knockdown resistance (kdr) is the main mechanism that confers resistance to pyrethroids and DDT. This is a product of non-synonymous mutations in the voltage-gated sodium channel (vgsc) gene, and these mutations produce a change of a single amino acid which reduces the affinity of the target site for the insecticide molecule. In Mexico, V410L, V1016I and F1534C mutations are common in pyrethroid-resistant Aedes aegypti (L.) populations. Methods A multiplex PCR was developed to detect the V410L, V1016I and F1534C mutations in Ae. aegypti. The validation of the technique was carried out by DNA sequencing using field populations previously characterized for the three mutations through allele-specific PCR (AS-PCR) and with different levels of genotypic frequencies. Results The standardized protocol for multiplex end-point PCR was highly effective in detecting 15 genotypes considering the three mutations V410L, V1106I and F1534C, in 12 field populations of Ae. aegypti from Mexico. A complete concordance with AS-PCR and DNA sequencing was found for the simultaneous detection of the three kdr mutations. Conclusions Our diagnostic method is highly effective for the simultaneous detection of V410L, V1016I and F1534C, when they co-occur. This technique represents a viable alternative to complement and strengthen current monitoring and resistance management strategies against Ae. aegypti.